THE DISTRIBUTION OF HARMONICS TRACTION CURRENT ALONG THE LENGTH OF THE FEEDER ZONE AND THEIR IMPACT ON THE OPERATION OF TRACK CIRCUITS - Serdiuk, T. M. (Science and Transport Progress, 2007)
The article considers issues of electromagnetic compatibility of traction network with the rail circuits. A mathematic model is elaborated for evaluation of distribution of harmonics of traction current on the length of feeder zone and determination of the value of stray currents. The results of modeling are represented for 50 and 100 Hz harmonics of return traction current.